2020
DOI: 10.1111/jgs.16981
|View full text |Cite
|
Sign up to set email alerts
|

Community Medication Education, Data, & Safety (C‐MEDS): Findings from a Pilot Project

Abstract: Objectives Medication‐related problems remain one of the largest health risks for older adults, yet there are few resources available to effectively reduce medication‐related problems for community dwelling older adults. The aim of this pilot program was to determine the effectiveness of a multifaceted medication intervention on medication adherence and self‐efficacy in medication use. Design A single sample, pre‐post‐test design. Setting This pilot study was conducted at Independence at Home, a Senior Care Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Where reported (in 26 out of 33 articles), the mean age of the participants varied from 67.8 years (SD = 7.8) 47 to 82.7 (SD = 6.4). 46 In a minority of studies, the intervention explicitly targeted patients taking multiple medicines 39 , 52 , 55 , 57 , 61 , 70 or living with multiple chronic conditions. 42 , 55 , 66 Some interventions targeted people with specific conditions such as congestive heart failure, 44 hypertension, 49 , 59 diabetes 69 and COPD 62 or taking specific types of medicines, e.g., anticholinergic, 47 anticoagulants 71 or antacids.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Where reported (in 26 out of 33 articles), the mean age of the participants varied from 67.8 years (SD = 7.8) 47 to 82.7 (SD = 6.4). 46 In a minority of studies, the intervention explicitly targeted patients taking multiple medicines 39 , 52 , 55 , 57 , 61 , 70 or living with multiple chronic conditions. 42 , 55 , 66 Some interventions targeted people with specific conditions such as congestive heart failure, 44 hypertension, 49 , 59 diabetes 69 and COPD 62 or taking specific types of medicines, e.g., anticholinergic, 47 anticoagulants 71 or antacids.…”
Section: Resultsmentioning
confidence: 99%
“… 46 In a minority of studies, the intervention explicitly targeted patients taking multiple medicines 39 , 52 , 55 , 57 , 61 , 70 or living with multiple chronic conditions. 42 , 55 , 66 Some interventions targeted people with specific conditions such as congestive heart failure, 44 hypertension, 49 , 59 diabetes 69 and COPD 62 or taking specific types of medicines, e.g., anticholinergic, 47 anticoagulants 71 or antacids. 58 Only one of the studies identified explicitly targeted older people living with frailty.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations